Pengaruh Kegiatan Melukis di Atas Garam untuk Mengembangkan Kreativitas pada Anak Usia Dini - Afrilia, Riri; Suryana, Dadan (Darul Yasin Al Sys, 2024)
This research is motivated by the fact that children’s creativity skilss are not yet optimal, which is caused by unattractive learning media and a lack of learning activities that are able to develop creativity in children. The aim of this research is to analyze the effect of painting on salt to develop creativity in young children. This research uses a quantitative methodology in the form of a quasi-experiment. This research was attended by all young children at the Kemala Bhayangkari 03 Alai Kindergarten, Padang City, totaling 77 children. This research sample was taken using a purposive sampling technique with a sample size of 24 children consisting of classes B3 and B6, each with 12 children. Data collection techniques use tests, observation and documentation with six statement items. Data analysis techniques were carried out by testing normality, homogeneity and hypothesis testing with the help of computerized SPSS.26. The average pre-test and post-test results in the experimental class were 13.08 and 19.58. Meanwhile, the average pre-test and post-test in the control class was 12.50 and 17.92. Based on the results of the research hypothesis test, it shows that the pre-test and post-test data for the experimental class show a Sig. (2-tailed) which is 0.007 < 0.05, so it is significant. Based on this, it can be concluded that the activity of painting on salt has a significant influence on developing creativity in early childhood at Kemala Bhayangkari 03 Alai Kindergarten, Padang City.